The Leishmania donovani IMPACT-like protein possesses non-specific nuclease activity - Rao, Shilpa J.; Shukla, Ekta; Bhatia, Varsha; Lohiya, Bharat; Gaikwad, Sushama M.; Kar, Anita; Pal, Jayanta K. (International Journal of Biological Macromolecules, 2018)
IMPACT (Imprinted and Ancient)-like proteins are known to be regulators of GCN2 (General control non-derepressible 2) kinases involved in translation regulation. Here, we report on cloning and characterization of an IMPACT-like protein, LdIMPACT from Leishmania donovani which harbours two domains. 'RWD domain' at the N-terminal end that mediates GCN2 regulation, while a conserved 'ancient domain' lies at the C-terminal end whose function remains elusive. Interestingly, our observations indicated that LdIMPACT has a novel nonspecific nuclease activity. In silico analysis further revealed the resemblance of ancient domain of LdIMPACT to RNase PH domain (known to bind to nucleic acids). The recombinant LdIMPACT exhibited a Mg2+-dependent nuclease activity. Moreover, thermostability and pH stability assays of the protein suggest it to be a stress responsive protein. Circular dichroism studies elucidated the conformational transitions of the enzyme in response to various temperature and pH conditions which correlated well with the activity profiles. Thus, the current study highlights the structural and functional characteristics of LdIMPACT which interestingly also possesses a novel nuclease activity. With its physiological relevance unresolved, the multifaceted LdIMPACT might therefore lie in a hitherto unknown network, whose perturbation could be an attractive therapeutic approach for treating leishmaniasis. (C) 2018 Elsevier B.V. All rights reserved.